OPTIMALISASI KINERJA KARYAWAN BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN JEPARA - Sisno Riyoko; Gun Sudiryanto (Universitas Islam Nahdlatul Ulama Jepara, 2011)
Work load is job responsibility which charged upon by a somebody wich must able to of better pursuant to at one particular organization.Way of this relevant with opinion in doing something that a few or a lot of owned with by all organizational member is all employees and head with its habit wich the ugly e ither or in working and at work Anorogo and Widiyanti (1993) expressing that if ampkoyees assessed to show the possibility of perfomance do not however its have potency.Matter that wai might possibly be happened by if jo environment do not support and the work load too is high felt by employees that result stress work.To be able to reach ideal employees perfomence like that require environmental support support existence of good job ,correct wor load its portion and the satisfaction work employees in a organizational. Research to test hypothesis of the purpose of agreing or strengthening hypothesis on the chance of,what in the end can strenghthen theory of taken as stepping .This research population is employees BAPPEDA Regency Jepara amounting to 53 people.While technique analysis data used [by][is] by Regresi Linier Berganda Path Analysis. Writer suggestion which can submit [is] 1)Form side of work load of officer require to doof evaluation to division work load to officer,among other things by : (a). Giving work adapted for skilled and the education and also mounth education of each officer,(b). Job Description givenly an work one who precisely 2) Creating job environment supporting officer by: (a). Routinely is conducted by activity with for all officer is so that created harmonius (b).Workroom settlement matching with lay out completion of task in BAPPEDA 3) Creating satisfaction work officer BAPPEDA,among other things by : (a) .Giving separate compensation of result of job . (b).attitude oaf a head. : (c). Behave fair specially in giving that good moment in the case of education to all 4) To increase the officer perfomence ,factor of satisfaction work officer have to bbepaid attention to among other things : (a) Improve facility of supporter with computerization .(b) Give incentive for officer owning achievement more compared to other ,so that able to give motivation for other officer to increase its perfomence.